Trends in digital newspaper discovery: a natural experiment. Issue 1 (4th January 2021) - Cribbs, Heather; Gardner, Gabriel J.; Holvoet, Katherine G.
Abstract: In this article, the discovery and use of digital newspaper collections are explored by capitalizing on a natural experiment that arose when five California State University libraries activated the Primo newspapers search interface, and five other libraries with similar enrollment numbers and comparable demographic profiles did not. By analyzing Primo Analytics data, COUNTER R4 data, and A–Z database list click-through data collected from the ten libraries over the course of academic years (AY) 2018–2019 (pre-deployment) and AY 2019–2020 (post-deployment), the effects on usage and legible user behavior of introducing a specialized Primo newspaper scope are calculated. Researchers explore how this research method can be a model for libraries to investigate trends within their own organizations.